Fabrication of Carum copticum essential oil–loaded chitosan nanoparticles and evaluation its insecticidal activity for controlling Rhyzopertha dominica and Tribolium confusum - Ziaee, Masumeh; Sheikhzadeh Takabi, Asiyeh; Ebadollahi, Asgar (Frontiers in Plant Science, 2023)
Plant essential oils (EOs) can be used as a feasible tool for insect pest control. Nanoparticle formulations of plant essential oils can improve the efficiency and stability of EOs, as well as insecticidal potential. In this study, Carum copticum L. essential oil-loaded nanoparticles (OLNs) were prepared via an oil-in-water emulsion, followed by droplet solidification via ionic gelation using a cross-linker, sodium triphosphate pentabasic (TPP). The nanoparticles were characterized by ultraviolet and visible (UV-Vis) spectrophotometry, Fourier transform infrared spectroscopy (FTIR), Laser light scattering (LS), Transmission electron microscopy (TEM), and scanning electron microscopy (SEM). Moreover, the insecticidal activity of C. copticum EO and OLNs was evaluated against Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) and Tribolium confusum Jacquelin du Val. (Coleoptera: Tenebrionidae). In addition, their effectiveness was assessed on the progeny production of tested insect species. The loading efficiency ranged from 34.33% to 84.16% when the chitosan to EO weight ratio was 1:1.25 and 1:0.5, respectively. The loading efficiency decreased with increasing EO content in the nanoparticles. The OLNs particles exhibited spherical shape. The particle size was in the range 120-223.6 nm, and increased with the increase of EO to chitosan ratio.So that the largest mean particle size (223.6 nm) was reported in the 1:1.25 weight ratio of chitosan to the EO. The mortality percentage of R. dominica and T. confusum adults were 74 and 57% when exposed for 7 days to 2000 mg/kg of OLNs at the 1:1.25 weight ratio, while EO caused 62 and 44% mortality on both insect species, respectively. Therefore, OLNs can potentially improve the insecticidal activity of C. copticum EO and could be applied to facilitate control of stored-products insect pests.